Seismic evidence for the existence of an entrained mantle flow coupling the northward advancing Indian plate under Tibet - Yu Zou; XiaoBo Tian; YouQiang Yu; Fa-Bin Pan; LingLing Wang; XiaoBo He (Earth and Planetary Physics, 2019)
The Tibetan Plateau, known as “the roof of the world” and “the third pole of the earth”, is a product of the collision between India and Asia during the last ~50 Ma. The regional tectonics–in particular, growth and expansion of the plateau–has been attributed primarily to deformation within the lithosphere. The role and pattern of the underlying asthenospheric flow, however, remain mostly unaddressed. In light of recent seismic tomographic images and published seismic anisotropic descriptions of the upper mantle, here we propose that an entrained mantle flow is likely to exist under Tibet, induced by the northward advancing Indian plate. The direction of mantle flow is characterized by a gradual rotation from northward in the south to eastward in the north as a result of deflection by the deep root of the Tarim block. The presence of an underlying mantle flow is not only able to account for the west-east oriented fast-axis of seismic anisotropy in northern Tibet, but can also adequately explain the sporadic null splitting in southern Tibet. Specifically, the null splitting results, at least in part, from upwellings of asthenospheric flow through tears of the underthrusting Indian plate that have been revealed by various seismic observations. The mantle flow may in turn promote the block extrusion under Tibet that has been observed in GPS measurements; hot asthenospheric upwellings may also lead to widespread post-collisional magmatism in southern Tibet.